Multidrug Resistant Acinetobacter Spp. Blood Stream Infection in A Neonatal Intensive Care Unit of An Urban Specialized Hospital in Dhaka (Journal of Dhaka Medical College, 2016)
Background: Acinetobacter spp. are ubiquitous in the environment, that is, soil and water, and occasionally isolated from mucous membrane, secretion, and skin of hospitalized patients, also on surfaces of hospital environment. Antibiotic resistant Acinetobacter spp. blood stream infection is a leading problem. Multidrug resistant Acinetobacter spp. blood infection in the neonatal intensive care unit (NICU) patients create a great problem in hospital settings.Methods: This study was carried out from January to December 2011 based on the clinical specimens obtained from suspected cases of septicemia patients admitted in the NICU of Addin Womens Medical College Hospital, Dhaka, Bangladesh. Blood collected from suspected cases by maintaining strict aseptic precaution and sent immediately to microbiology laboratory of the same institution. Samples were also taken from different sites in NICU and Department of Obstetrics & Gynaecology operation theatre for detection of the sources of infection in outbreak situation. Isolated organisms were identified by standard bacteriological method and drug susceptibility test had been done by modified Kirby Bauer disk diffusion technique.Results: A total 87 blood culture positive cases were included in this study. Out of 87 culture positive cases Acinetobacter spp. was the predominant pathogen 32 (35.58%). Acinetobacterspp isolated from the blood of newborn and the mortality rate was 3.33%. Acinetobacter blood stream infection is more common in the first 7 days of life (early onset) , birth weight less than 2 kg ( 56.6%), also affected the baby with birth weight more than 2.5 Kg (23.3%) and most of the neonates having gestational age less than 37 weeks (70%). Twenty four babies (80%) were delivered in the same hospital. Acinetobacter spp. showed increased resistance against majority of antibiotics such ascolistin 3.12%, levofloxacin 40.62%, imipenem 53.12%, cotrimeoxazole 54.54%, pipericillin tazobactum 59.37%, amikacin 75%, ciprofloxacin 78.12%,gentamycin 84.37%, amoxyclavulonic acid 93.75%, ceftriaxone, ceftazidime and cefixime 96.87% cefuroxime, cephradineand ampicillin 100% respectively. We categorized the Acinetobacter spp. in to 3 categories, such as multidrug resistant (MDR) 37.5%, extensive drug resistant (XDR) 28.12% and pandrug resistant (PDR) 3.12% Miscellaneous pattern of sensitivity 31.15%. A cluster of cases occurred in month June, which was quite higher than other months, Surveillance had been done. Acinetobacter spp. isolated from the environment of operation theatre of Obstetrics and Gynea department. In NICU, Acinetobacter spp were isolated from suction water, suction tube, incubator door handle and body surface of the neonates. Acinetobacter spp. which were isolated from suction tube and suction water were only sensitive to colistin and resistant to other drugs. Two Acinetobacter spp. were alsoisolated from OT environment and body surface of neonates which were found sensitive to only imipenem and colistin. Acinetobacter spp. isolated from incubator door handle was sensitive to colistin, imipenem, amikacin, gentamycin, levofloxacin, ciprofloxacin, piperacillin tazobactum and cotrimoxazole.J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 47-52